2017
DOI: 10.1097/igc.0000000000001101
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-Assisted Radical Hysterectomy Results in Better Surgical Outcomes Compared With the Traditional Laparoscopic Radical Hysterectomy for the Treatment of Cervical Cancer

Abstract: ObjectiveThe aim of this study was to compare the surgical outcomes of robotic-assisted radical hysterectomy (RRH) with traditional laparoscopic radical hysterectomy (TLRH) for the treatment of early-stage cervical cancer in a large retrospective cohort of a total of 933 patients.MethodsWe have enrolled 100 patients into the RRH and 833 patients into the TLRH group. The surgical outcomes include operating time, blood loss, transfusion rate, pelvic lymph node yield, hospitalization days, duration of bowel funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Retrospective and prospective studies of sexual function after open RH demonstrate impaired sexual desire, arousal, and satisfaction . In addition, urination problems and bowel dysfunction occur frequently, not only after open RH but also after laparoscopic surgery . However, few studies have investigated the effect of robot‐assisted laparoscopic radical hysterectomy (RRH) on sexual, bladder, and bowel functions.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective and prospective studies of sexual function after open RH demonstrate impaired sexual desire, arousal, and satisfaction . In addition, urination problems and bowel dysfunction occur frequently, not only after open RH but also after laparoscopic surgery . However, few studies have investigated the effect of robot‐assisted laparoscopic radical hysterectomy (RRH) on sexual, bladder, and bowel functions.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 20 controlled studies on LRH and RARH that we identified in PubMed, up to December 2017, with ‘robot’ and ‘radical hysterectomy’ as search terms, nine studies included reports on 30 or more cases of RARH (Table ) . Generally in these studies, the volume of blood loss was smaller for RARH than LRH, with no conclusions on the relative merits in terms of short‐term perioperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…were the first to report on robot‐assisted radical hysterectomy (RARH) with lymph node dissection, in 2006 . Since then, several studies have compared conventional laparoscopic radical hysterectomy (LRH) and RARH, with comparable short‐term outcomes having been reported for both procedures, including estimated blood loss, operative time, complications and the number of resected lymph nodes …”
Section: Introductionmentioning
confidence: 99%
“…However, RH proved to be more profitable in complex procedures, obese patients, and in uterine weights >750 g [30,31]. The price per patient is also expected to drop with increased RH use and surgeon experience [33].…”
Section: Costmentioning
confidence: 99%